Current management of non-alcoholic fatty liver disease - LISBOA,QUELSON COELHO (2016)
SUMMARY Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic accumulation of lipid in patients who do not consume alcohol in amounts generally considered harmful to the liver. NAFLD is becoming a major liver disease in Eastern countries and it is related to insulin resistance and metabolic syndrome. Treatment has focused on improving insulin sensitivity, protecting the liver from oxidative stress, decreasing obesity and improving diabetes mellitus, dyslipidemia, hepatic inflammation and fibrosis. Lifestyle modification involving diet and enhanced physical activity associated with the treatment of underlying metabolic are the main stain in the current management of NAFLD. Insulin-sensitizing agents and antioxidants, especially thiazolidinediones and vitamin E, seem to be the most promising pharmacologic treatment for non-alcoholic steatohepatitis, but further long-term multicenter studies to assess safety are recommended.